Enkapsulasi Probiotik Lactobacillus sp.Menggunakan Dua Tahap Proses - Rintan Fransiska Trimudita; Djaenudin Djaenudin (Fakultas Teknik, 2021)
The Lactobacillus sp. a probiotic microorganism that can’t to survive gastric acidity and the concentration of bile salts in the gastrointestinal tract. Probiotic encapsulation is one of the methods to protect probiotic during processing process, storage, and from acidic solutions in the gastrointestinal tract. The research was to know that viability was encrypted with an alginat matrix and we were against testing in simulated stomach acid. In this research, the encapsulation process was conducted by mixing Lactobacillus sp. with Na-Alginate to form a suspension as encapsulation material. The microcapsules formed were coated with chitosan with concentrations i.e., 1.2%; 1.6%; and 2%. Lactobacillus sp. encapsulated chitosan matrix was tested for its viability in gastric fluid simulation (0,2% NaCl pH 1,2 and 3) for 1 minute, 60 minutes and 120 minutes using the TPC method (Total Plate Count). After the viability test, Lactobacillus sp. encapsulated with 2% chitosan could maintain the viability lactobacillus sp with the number of colony was of 7,41 log Cfu/gram in the simulation of gastric acid fluid pH 3 for 120 minutes, and 4,78 log Cfu/gram in the simulation gastric acid fluid pH 1,2 with duration 120 minutes.